The evaluation of risk factors of genesis of plural caries in children with pathology of gastrointestinal tract - M. A. Luchynskyi; V. I. Rozhko (Kazimierz Wielki University, 2017)
The substantial risk factors of development of plural caries in children with gastrointestinal diseases are toxicosis of pregnancy, extragenital mother diseases, children diseases of junior age,inferior feed, irregular oral hygiene. The research aim was to study risk factors of genesis of plural caries in children with gastrointestinal diseases.For thedecision of aim were inspected260 children 6‒15-years-old.The result of undertaken studies: a relative risk ofdevelopment of caries at pathology of pregnancyand luingins in children with a plural carieswas in 1,4 times higher thanfor childrenwithout pathology.In the same time, functional disorders of GIT,oligotrophyand rachitis, children diseases of junior age ensure development of thedecompensated form of caries,with a relative risk,in 2,25 timeshigher than for childrenwithout mentionedpathologies.